Augmented BIM workflow for structural design through data visualization. - Boechat, Luiza Carneiro (2021)
It has been decades since the impact of information technology (IT) on structural engineering started to be discussed. The first documentation and analysis software prototypes date from the 1950s and 1960s. In the 90s, a survey indicated that a great number of structural engineers already agreed that IT was accelerating engineering. This close relationship evolved with the increasing power of computation. Nowadays, it is possible that engineers explore an amplified design space before reaching a final solution, mainly through parametric modeling combined with analysis. This culminated in large and complex data being generated during design. At the same time, the popularization of Building Information Modeling (BIM) and its focus on information present an opportunity for engineers to use BIM models as databases for enhancing design and collaboration. To fully leverage this data, it is imperative to condense it into meaningful and actionable visualizations. In this context, this research investigates and tests a workflow for structural design in BIM, named an \"augmented BIM workflow for structural engineering through data visualization\". The general objective is the enhancement of collaboration within a design team. A computational tool for enabling this workflow is proposed and implemented at a proof of concept (PoC) level, combining data from FEA (Finite Element Analysis) and BIM models. Extraction, transformation, and load processes from these data sources into a data warehouse in a visualization software solution are executed. The proposal was presented to engineers and BIM specialists. Feedback was collected to base the construction of a set of standard dashboards for data visualization. The final dashboards had their utility validated by the professionals. Technical limitations on the current implementation and underlying barriers to adoption are discussed.